The Morphological, Clinical and Radiological Outputs of the Preclinical Study After Treatment of the Osteochondral Lesions in the Porcine Knee Model Using Implantation of Scaffold Based on the of Calcium Phosphate Biocement - Vdoviaková, Katarína; Danko, Ján; Krešáková, Lenka; Šimaiová, Veronika; Petrovová, Eva; Novotný, Jaroslav; Žert, Zděnek; Koľvek, Filip; Valocký, Igor; Varga, Maroš; Špakovská, Tatiana; Pribula, Jozef; et al. (Frontiers in Materials, 2021)
The symptomatic full-thickness cartilage lesions or cartilage degeneration leads to the destruction of the normal chondral architecture and bone structure in affected area, causes the osteoarthritis, and general damage to the health. Knee joints are most frequently affected by this condition. The permanent damage of the articular cartilage and subchondral bone has motivated many scientists and clinicians to explore new methods of regeneration of osteochondral defects, such as novel materials. We studied the potential of the biocement based on calcium phosphate consisting of a mixture of four amino acids (glycine, proline, hydroxyproline and lysine) in the regenerating process of the artificially created osteochondral defect on the porcine medial femoral condyle in the stifle joint. The mass ratio of the amino acids in biocement CAL was 4:2:2:1. The Ca/P ratio in cement was 1.67 which correspond with ratio in hydroxyapatite. We compared the results with spontaneous healing of an artificially created cyst with that of the healthy tissue. The animal group treated with biocement paste CAL presented completely filled osteochondral defects. The results were confirmed by histological and radiological assessments, which have shown regenerated chondral and bone tissue in the examined knee joints. Macroscopic evaluation showed that neocartilage was well integrated with the adjacent native cartilage in animal group with biocement CAL, compared with healing of the artificial cyst, where treated cartilage surfaces were visibly lower than the surrounding native cartilage surface and a border between native and restored tissue was apparent. The qualitative assessment of the implant histology specimens showed full regeneration of the hyaline cartilage and subchondral bone in animals with biocement CAL. The artificial cyst group showed remarkable fibrillation. The detailed MRI analysis of cross-section of osteochondral defect confirmed the complete cartilage and subchondral bone healing where the thickness of the regenerated cartilage was 1.5 mm.